Excessive length of iliac arteries in athletes with flow limitations measured by magnetic resonance angiography - Schep, G.; Kaandorp, D. W.; Bender, M. H.; van Engeland, S.; Weerdenburg, H.; Titulaer, B. M.; Wijn, P. F. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: Kinking of the iliac arteries can cause flow limitations in endurance athletes. Such kinking may be treated by surgical release of the iliac arteries. However, when the length of the iliac artery is excessive, this may not be effective. Because threshold values of excessive length of the iliac arteries are unknown, normal values for endurance athletes were obtained and abnormalities encountered in these patients are reported. METHODS: Forty-three endurance athletes (46 symptomatic legs) with flow limitations in the iliac arteries were examined using magnetic resonance angiography (MRA) with hips extended and flexed. The ratio of vessel length to straight-line distance was determined for the common and external iliac arteries. Sixteen national-level cyclists (32 reference legs) served as a control group. RESULTS: For the common iliac artery, length ratios were significantly (P < 0.05) higher in the symptomatic legs than in the reference legs (symptomatic legs: 1.1 +/- 0.12, 1.22 +/- 0.19, reference legs 1.05 +/- 0.04, 1.11 +/- 0.05 with extended and flexed hips, respectively). For the external iliac artery, only in the position with hips flexed, the ratios in the symptomatic legs were significantly higher than in the reference legs (symptomatic legs: 1.11 +/- 0.09, 1.44 +/- 0.23, reference legs 1.08 +/- 0.05, 1.32 +/- 0.13 with extended and flexed hips, respectively). A small proportion of symptomatic legs had extremely high length ratios. CONCLUSION: MRA is effective for determining vessel length. The ratio of vessel length to straight-line distance with extended and flexed hips is a good measure for excessive vessel length and achieves extreme values in a small subgroup of patients. Further prospective study is warranted to define maximal vessel length ratios, which still allow benefit from surgical release of the iliac arteries.